‘Play And Playing’- Cross-reading The East-coast Bajau’s Ritual Performances as A Traditional Theater Performance - Sharifuddin Zainal; Mohd Kipli Abd Rahman; Esterlina Moo Chin Len Lazarus; Muhamed Syafiq Salleh; Amsalib Pisalie; Mohamad Nor Hisyam Musa (Penerbit UMS, 2023)
The East-Coast Bajau ethnic group is clustered into the Bajau Laut ethnic division. Having a sea centered belief, the spirits of ancestor (Keombo’an) and the spirits of nature - these formerly pagan ethnic groups have achieved a syncretism of beliefs since the emergence of Islam. These changes in beliefs have been a factor in the occurrence of liminal processes; in their practice and beliefs of the sacred traditional healing ritual performances to the more secular form of traditional theater. The terms of 'play and playing' is a familiar term and a common practice of the traditional theater performances in which instead of acting, the performers play the role in accordance with its spontaneous and improvisational features. The playing skills of the traditional theater players (instead of performers) are always tested with their ability to develop performances based only on a given storyline. The elements of ‘play and playing’ are also an important part to the performance structure of the Bajau Laut’s healing ritual, most of which consist of secular elements in the ritual performances. The ‘play and playing’ element in the ritual performance is seen as the aesthetic potential of the Sabah’s indigenous traditional theater. This paper aims to synthesize the liminal performance of the Bajau’s traditional ritual as a traditional theater performance text. Through the crossreading towards ‘Victor Turner’s-ritual theory’ and ‘Richard Schechner-performance theory’, the discourse analysis on the elements of ‘play and playing’ was carried out to obtain and to unfold the traditional theatrical features of the Bajau.